2007
DOI: 10.2325/jbcs.14.401
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of dose-response curve for paclitaxel in breast cancer

Abstract: An individual dose-response curve for paclitaxel in breast cancer can be obtained using the HDRA technique. Nuclear grade 3 tumors appeared to have more uniform chemosensitivity to paclitaxel compared with nuclear grade 1 and 2 tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…The drug concentration-cell growth (that is, dose–response) curve is generally not linear, and ideally should be logistic. To evaluate drug sensitivity, the curve must show a logistic curve that is considered to be a pharmacological drug response [12,15]. We confirmed that hyperbolic dose–response curves are a sufficient indicator of drug resistance.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The drug concentration-cell growth (that is, dose–response) curve is generally not linear, and ideally should be logistic. To evaluate drug sensitivity, the curve must show a logistic curve that is considered to be a pharmacological drug response [12,15]. We confirmed that hyperbolic dose–response curves are a sufficient indicator of drug resistance.…”
Section: Discussionsupporting
confidence: 60%
“…Rigid quantitation by conventional chemosensitivity assays has been quite challenging because the number of available tumor cells from solid tumors is extremely limited, which precludes the construction of drug dose–response curves from tumor cells [11,12]. The results from a limited number of data points may not be of sufficient quality for measuring the non-linear associations between drug dose and cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Good correlations between efficacy rate for an individual agent using HDRA in vitro assay and clinical response rate to each agent have been reported previously. These findings suggest that chemosensitivity determined from HDRA with MTT endpoint probably reflects chemosensitivity in vivo and would be suitable for clinical applications and are congruent with a number of prior studies reporting HDRA as a useful predictor for response to chemotherapy in various cancer (25)(26)(27)(28). These results show that HDRA allows conservation of the original phenotypic characteristics of tumor cells.…”
Section: Discussionsupporting
confidence: 76%
“…More recently, Furukawa et al (23) reported that HDRA with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H tetrazolium bromide (MTT) endpoint is clinically useful for chemosensitivity assay in the field of gastrointestinal surgery field. Although several studies have investigated the efficacy of HDRA with MTT endpoint in a variety of cancers (24)(25)(26)(27)(28), little work has been done to elucidate the clinical utility of HDRA with MTT endpoint for esophageal cancer (29).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition rate at single concentrations is also not so varied. [15][16][17] For gefi tinib in our study, the 12 patients without dose-response curves probably did not have any sensitizing gene mutation in EGFR or had some gefi tinib-resistant molecular features.…”
Section: Discussionmentioning
confidence: 97%